2000
DOI: 10.1007/s004420000458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature-induced variation in anuran larval growth rate on head width and leg length at metamorphosis

Abstract: We tested whether temperature-induced variation in the growth rate of Rana cascadae tadpoles caused any variation in head width or leg length at metamorphosis, independent of the effects of temperature on body size. Body-size-adjusted head width appears to be insensitive to even large variations in tadpole growth rate. This result mirrors previous observations on the effects of variation in food level and temperature on metric shape in frogs and other ectothermic vertebrates. Leg length, on the other hand, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 45 publications
4
64
0
1
Order By: Relevance
“…Interestingly, increasing temperature did not induce a response in hind leg length with an effect size not different from zero. Although developmental time was clearly reduced and growth rate was enhanced, an expected hind leg elongation similar to that found with increasing resources was only found for ranid frogs (Rana cascadae, Blouin & Brown 2000;and R. lessonae, Orizaola & Laurila 2009), whereas a shortening in hind legs was found for the rest of species. This contrasting pattern may reflect a phylogenetic signal, although the small sample size (6 species) precludes any power in the statistical analysis of phylogenetic autocorrelation (Abouheif 1999).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Interestingly, increasing temperature did not induce a response in hind leg length with an effect size not different from zero. Although developmental time was clearly reduced and growth rate was enhanced, an expected hind leg elongation similar to that found with increasing resources was only found for ranid frogs (Rana cascadae, Blouin & Brown 2000;and R. lessonae, Orizaola & Laurila 2009), whereas a shortening in hind legs was found for the rest of species. This contrasting pattern may reflect a phylogenetic signal, although the small sample size (6 species) precludes any power in the statistical analysis of phylogenetic autocorrelation (Abouheif 1999).…”
Section: Discussionmentioning
confidence: 64%
“…We estimated adjusted mean differences in morphology between environments by using analysis of covariance (GLM module,STATISTICA 8.0,Statsoft) (Blouin & Loeb 1991) and Rana cascadae (Blouin & Brown 2000), snout -vent length (SVL) (mm) was employed as covariate, and the first principal component (PC1) was used as a covariate in Discoglossus galganoi (Nicieza et al 2006). The environment -body size interaction term was included in the model to test for heterogeneity of slopes.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in frogs from density experiments the early metamorphosing individuals have higher ratios of hind-limb to SVL than do the later metamorphosing individuals, so that time to metamorphosis and relative hind-limb size show a negative phenotypic correlation (Emerson 1986; but see Blouin and Loeb 1991). Blouin and Brown (2000) demonstrated that the cold-induced extension of the larval period in Rana cascadae results in shorter relative tibio-fibula lengths at metamorphosis. Therefore, the lower jumping performance of coldreared individuals can result from an alteration in metamorph morphology.…”
Section: Discussionmentioning
confidence: 95%
“…The environmental conditions experienced by larvae can have consequences on postmetamorphic success not only through indirect effects derived from changes in metamorphic traits (Smith 1987), but through their direct effects on traits influencing survival and growth in juvenile stages (Scott 1994). In ectotherms, temperature experienced during embryonic development has been shown to affect juvenile shape (Swain and Lindsey 1986;Shine and Harlow 1993;Blouin and Brown 2000), trunk segmentation (Tåning 1952;Lindsey and Harrington 1972) and muscle structure (Stickland et al 1988;. Moreover, phenotypic variation in these traits has a significant impact on locomotor performance (Swain 1992a;Shine and Harlow 1993;Tejedo et al 2000a) and is subjected to strong selection associated with predation (Swain and Lindsey 1984;Swain 1992aSwain , 1992b.…”
Section: Introductionmentioning
confidence: 98%